PENGARUH MODEL PEMBELAJARAN TALKING STICK TERHADAP HASIL BELAJAR SISWA KELAS V PADA PEMBELAJARAN TEMA 2 SUBTEMA 1 DI UPTD SD NEGERI 122357 JL.JATI PEMATANG SIANTAR - Banjarnahor, Yolanda Gabriyela; Sihombing, Lisbet Novianti; Sijabat, Desi (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2023)
The purpose of this research was to determine the influence of the Talking Stick Learning Model on the Learning Outcomes of Class V Students. This research method is an experimental method with a Pre-Experimental design type using a One Group Pretest Posttest Design design. The number of samples is all class V students at UPTD SD Negeri 122357 Jl. Jati, totaling 30 students. Data collection was carried out using test and observation techniques. Research data was analyzed using statistical and inferential analysis. Based on the data results, it is known that ttable is 1.699, tcount is 12.6638, significant 0.05. So it can be concluded that there is an influence of the Talking Stick Learning Model on Student Learning Outcomes in Learning Theme 2 Subtheme 1 at UPTD SD Negeri 122357 Jl. Teak Pematang Siantar. This shows that Ha is accepted and H0 is rejected. Based on the results of the data presented, the researcher concluded that the student learning outcomes before being given treatment, all students still had not reached the KKM, namely 30 students (100%) and after being given treatment, student learning outcomes increased, namely 27 students (90% ) has a value above the KKM.